Gambaran Indeks Eritrosit pada Pasien Penyakit Ginjal Kronik yang Menjalani Hemodialisis di RSUP H. Adam Malik Medan - Yosephin Irene Togatorop; Nindia Sugih Arto (Fakultas Kedokteran, Universitas Andalas, 2022)
Chronic Kidney Disease (CKD) will cause anemia which can lead to death. CKD patients undergoing hemodialysis therapy can also experience anemia. Therefore, it is necessary to check the erythrocyte index consisting of Mean Corpuscular Volume (MCV), Mean Corpuscular Hemoglobin (MCH), and Mean Corpuscular Hemoglobin Concentration (MCHC) to determine the type of anemia so that appropriate therapy can be given. Objectives: To determined the description of the erythrocyte index in CKD patients undergoing hemodialysis at H. Adam Malik General Hospital Medan. Methods: This research used the descriptive observational method with a cross-sectional design. The study population was all CKD patients who underwent hemodialysis at the Adam Malik General Hospital Medan period July 2018 until June 2019 according to inclusion and exclusion criteria (total sampling) using medical record data. Results: From 149 study samples, 92 people (61.7%) were male, 57 people were female (38.3%), more in the age range of 55-64 years, hemoglobin (Hb) on average in low grades (98.9% men, 94.7% women), and erythrocyte index (MCV, MCH, MCHC) averages in the normal range. Conclusion: The description of patients with chronic kidney disease undergoing hemodialysis at H. Adam Malik General Hospital in July 2018 - June 2019, in general, is normochromic normocytic anemia.Keywords: CKD, erythrocyte index, Hb, hemodialysis